2015
DOI: 10.1039/c4ra14813d
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethylpullulan promoted Cu2O-catalyzed Huisgen-click reaction

Abstract: Cu2O/CMP has been developed as a highly efficient catalytic system for Huisgen-click reaction in water at 60 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
(11 reference statements)
0
4
0
1
Order By: Relevance
“…However, drawbacks are obvious, because of the unrecoverable and unreusable properties of small molecular organic acids. In order to overcome these problems, the authors latter on combined Cu 2 O and carboxymethylpullulan (CMP) for high-yield CuAAC reactions in water with a relatively short reaction times, and CMP still remained in water enabling easy recoverability and reusability [144]. Very recently, Cu 2 O supported on graphene nanosheet [145] served as recyclable and reusable heterogeneous catalyst with excellent catalytic activity for CuAAC.…”
Section: Cuaacmentioning
confidence: 99%
“…However, drawbacks are obvious, because of the unrecoverable and unreusable properties of small molecular organic acids. In order to overcome these problems, the authors latter on combined Cu 2 O and carboxymethylpullulan (CMP) for high-yield CuAAC reactions in water with a relatively short reaction times, and CMP still remained in water enabling easy recoverability and reusability [144]. Very recently, Cu 2 O supported on graphene nanosheet [145] served as recyclable and reusable heterogeneous catalyst with excellent catalytic activity for CuAAC.…”
Section: Cuaacmentioning
confidence: 99%
“…We invoked the mechanism based on the following considerations. (i) Much like CuO, it has been shown in several reports that Cu 2 O is also capable of catalyzing the click synthesis. (ii) However, our optimization studies using Cu 2 O (Table , entry 10) have resulted only in trace amounts of the product. Incidentally, Michaud et al also observed the lack of catalytic activity for Cu 2 O toward click chemistry .…”
Section: Resultsmentioning
confidence: 95%
“…Interestingly, the Cu(OAc) 2 to Cu 2 O-NPs conversion co-produced HOAc as by-product, that suggested the beneficial role of acidic media for the CuAAC reaction to proceed [73]. Built on these observations, the same group developed the fast and high-yielding 1,3-dipolar cycloaddition of organic azides with terminal alkynes catalyzed by Cu 2 O (0.5 mol%) in neat water using carboxymethylpullulans (CMP; 5 mol%) as a mild source of protons (see Scheme 9c) [74]. Remarkably, the Cu 2 O/CMP catalytic system was efficiently recycled up to 6 consecutives runs, and might be recycled six additional runs upon acidic treatment that reactivates the CMP co-catalyst.…”
Section: Cu-catalyzed 13-dipolar Cycloaddition Of Azides and Alkynes (Cuaac) In Watermentioning
confidence: 99%